36th AIAA Thermophysics Conference 2003
DOI: 10.2514/6.2003-4187
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Spreading Resistances in Rectangular Flux Channels: Part I Geometric Equivalences

Abstract: This paper presents a simple geometric tramsformation for predicting thermal spreading resistance in isotropic and compound rectangular flux channels using the solution for an isotropic or compound circular flux tube. It is shown that the results are valid for a wide range of channel aspect ratios and source to base coverage ratio. Since the circular disk solution requires a single series summation, it is preferable to the rectangular flux channel solution which requires the evaluation of two single series and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…In addition to these new solutions, the effect of shape was recently examined by the authors. Muzychka et al 11 showed that the thermal spreading resistance was a weak function of shape and geometry. Equivalency was established between the flux tube and the flux channel.…”
Section: Flux Channelsmentioning
confidence: 99%
“…In addition to these new solutions, the effect of shape was recently examined by the authors. Muzychka et al 11 showed that the thermal spreading resistance was a weak function of shape and geometry. Equivalency was established between the flux tube and the flux channel.…”
Section: Flux Channelsmentioning
confidence: 99%
“…Spreading thermal resistance also exists when heat is conducted from disc 2 to disc 3. Spreading thermal resistance of disc 2 is calculated using the following expression [15], which depicts the explicit relationship with the geometry of the structure, according to the notion in Fig. 4.…”
Section: Calculation Of R Copmentioning
confidence: 99%
“…When heat is conducted from the TIM to the aluminium stage or from the aluminium stage to the copper heat sink, there are spreading thermal resistances that comprise major portions of R alu and R cop . Muzychka et al [15] studied spreading thermal resistance in isotropic flux channels with rectangular heat source and isotropic discs with a circular heat source. The expressions for calculating spreading thermal resistance of the two systems were obtained.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermal spreading resistance theory is found to have widespread applications in electronics cooling, both at the board and chip level. These include, but are not limited to, the prediction of thermal resistance of electronic devices known as ball grid arrays [7], the effect of heat source eccentricity [8], the effect of heat spreaders in compound systems [9][10][11][12], the effect of orthotropic properties [13,14], and the issues of contact shape and edge cooling [15][16][17]. In a multi-chip packaging, huge heat generated from the LED chips is conducted through heat slug to the printed circuit board, and finally is transferred from the heat sink to environment.…”
Section: Introductionmentioning
confidence: 99%